Abdullah Eteng: His Struggles and Achievements for Indonesia and North Sumatra - Yushar Tanjung; Pulung Sumantri; Adam Zaki Gultom (JUSPI (Jurnal Sejarah Peradaban Islam), 2021)
This article discusses Abdullah Eteng, a local fighter from North Sumatra who was instrumental in securing the Republic of Indonesia's independence. This research employs a historical method. Because this study is centered on Abdullah Eteng, this article takes on the form of a biography. Abdullah Eteng is a fighter who demonstrates consistency in the pursuit of his ideals. The struggle spanned multiple eras, including Dutch colonialism, Japan, the Physical Revolution, the Old and New Orders. From the ground up, he forged himself to the pinnacle of his career. Throughout his life, he was involved in organizations and the news media and possessed a strong sense of responsibility. As a bureaucrat, he is accountable to political parties and members of parliament.